Genotypes and different clinical variants between children and adults in progressive familial intrahepatic cholestasis: a state-of-the-art review - Giovanni Vitale; Marco Sciveres; Claudia Mandato; Adamo Pio d’Adamo; Angelo Di Giorgio (Orphanet Journal of Rare Diseases)
Abstract Introduction Progressive Familial intrahepatic cholestasis (PFIC) are rare disorders of bile acid (BAs) secretion and transport with a genetic background. PFIC are paediatric manifestations, but the same variants causing PFIC can also cause cholestasis with a later paediatric onset or adult-onset cholestatic disease (AOCD). Pruritus is a symptom of cholestasis that can be so devastating that it requires a liver transplant (LT) in children; some PFIC types have been described as at risk of liver cancer development. Commonly prescribed medications for PFIC symptoms can partially relieve pruritus without changing the natural history of the disease. Recently, a therapy reducing the intestinal resorption of BAs has been approved; it is effective on both pruritus and cholestasis in PFIC, potentially being a disease-modifying intervention. Areas covered The clinical and genetic characteristics of different PFIC and AOCD are summarized to provide a common background for geneticists and paediatric and adult hepatologists in diagnosis and management. Expert opinion Collaboration between paediatric and adult hepatologists and geneticists will become crucial for cholestatic disease research and patient treatment. Therefore, adult hepatologists will need to learn more about FIC. This might enable the implementation of individualized surveillance in FIC patients and the evaluation of patient family histories.